Injection compression moulding (ICM) process development for the warpage and stress reduction on polymeric microfluidic chip applications - Lee, Jia Min (2018)
The vast range of applications of microfluidic chips has propelled the growth of the microfluidic industry for thinner, more precise and complex microfluidic chips, thus the need for high precision fabrication technique capable of mass fabrication grows with this rising demand. Hesitation effects and defects like warpage and short shot are common in thin microfluidic chips with high aspect ratios. This report will introduce a high precision fabrication technique– injection compression moulding (ICM) and compare its filling characteristics with the widely used conventional injection moulding (CIM). In addition, the report will document the need for ICM modifications of mould design, effects of process parameters on final part and the replication accuracy and repeatability of the moulding techniques. Using simulation, the proposed ICM demonstrated large improvements in replication accuracy and warpage from 15% up to 38% as compared with CIM. From experimental results, ICM has shown to be highly capable in repeatability and replication accuracy, with minimal deviations from the mould inserts.